Endoscopic submucosal dissection combined with clip for closure of gastrointestinal fistulas including those refractory to previous therapy - Lafeuille, Pierre; Wallenhorst, Timothée; Lupu, Alexandru; Jacques, Jérémie; Lambin, Thomas; Camus, Marine; Yzet, Clara; Ponchon, Thierry; Rostain, Florian; Rivory, Jérôme; Subtil, Fabien; Pioche, Mathieu (Endoscopy, 2021)
Background Gastrointestinal (GI) fistula is a life-threatening condition and a therapeutic challenge. Endoscopic approaches include mucosal abrasion, clip closure, or stent diversion, with moderate success rates in the long term. We assessed whether fistula endoscopic submucosal dissection with clip closure (FESDC) could lead to complete resolution of fistulas even after failure of previous endoscopic therapy.Methods Patients with GI fistulas, including those with previous failed treatment, were retrospectively included. The primary outcome was long-term (> 3 months) success of fistula healing. Secondary outcomes included technical success, safety, and factors associated with FESDC success.Results 23 patients (13 refractory 57 %) were included. Tight immediate sealing was achieved in 19 patients (83 %; 95 % confidence interval [CI] 61 %–95 %). Long-term closure was achieved in 14 patients (61 %; 95 %CI 39 %–80 %), with median follow-up of 20 months. Complications occurred in two patients (9 %). Previous local malignancy (P = 0.08) and radiotherapy (P = 0.047) were associated with a higher risk of failure.Conclusion This novel FESDC strategy was demonstrated to be safe and feasible for permanent endoscopic closure of GI fistulas. Further studies are warranted to determine the place of this technique in the management of chronic GI fistula.